BUDAYA KOMUNIKASI MASYARAKAT PERKOTAAN: (Ditinjau dari Aspek Sosiologi dan Antropologi Komunikasi) - Bob Andrian (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Many experts believe that in the sociological paradigm an order of community life is dynamic in nature, in accordance with the factors that shape the social construction of the community itself. These factors include those contained in the social order itself, ethnicity, race, religion, culture, type of work, level of education, social status, and other elements. These elements will be an important factor in shaping cultures in society. Included in it is the mainstay culture between elements of society, which is then known as the culture of communication. In terms of general aspects, the classification of society is very diverse. Some are known as peripheral communities, border communities, industrial societies, laborers, even including the academic community. However, in terms of geography or demography, there are two classifications of society, namely rural communities and urban communities. Where in between, inspiration certainly has differences and characteristics of each, especially in the cultural aspects, namely the culture of communication.